2011
DOI: 10.1016/j.otsr.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Pelvis and total hip arthroplasty acetabular component orientations in sitting and standing positions: Measurements reproductibility with EOS imaging system versus conventional radiographies

Abstract: Level III. Prospective diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 19 publications
7
90
0
17
Order By: Relevance
“…Stratified by pincer size, rotation, and tilt, the intermodality ICCs showed excellent reliability between EOS 1 and conventional radiography in morphologic features of the pincer. Our study also is consistent with previous EOS 1 imaging studies, which all showed an image quality of EOS 1 comparable to improved compared with that of conventional radiography [1,6,17,18,20,24,31]. However, we did see relative horizontal widening of the image in EOS 1 with extreme anterior tilt (C 10°) and horizontal narrowing in extreme posterior tilt (C 10°) owing to the decrease or increase in distance between the x-ray beam and the pelvis (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Stratified by pincer size, rotation, and tilt, the intermodality ICCs showed excellent reliability between EOS 1 and conventional radiography in morphologic features of the pincer. Our study also is consistent with previous EOS 1 imaging studies, which all showed an image quality of EOS 1 comparable to improved compared with that of conventional radiography [1,6,17,18,20,24,31]. However, we did see relative horizontal widening of the image in EOS 1 with extreme anterior tilt (C 10°) and horizontal narrowing in extreme posterior tilt (C 10°) owing to the decrease or increase in distance between the x-ray beam and the pelvis (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Radiation doses of EOS 1 have been reported as eight to 10 times less than conventional radiography and 800 to 1000 times less than CT [15,20,31]. A couple studies have validated the use and reliability of EOS 1 in imaging of the hip and lower extremities [18,31]. At this time, we are unaware of any studies showing the ability of EOS 1 to reliably measure established hip parameters in morphologic pincer features at varying degrees of tilt and rotation [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have measured pelvic tilt in patients undergoing THA during sitting and standing positions, usually reporting values similar to ours with mean standing sacral slope angles between 35°and 40°, and mean sitting sacral slope angles between 14°and 24° [19,22,26]. Our study is the first, to our knowledge, to stratify patients undergoing THA into those with or without lumbar DDD, and we found that most patients with DDD had flattened backs (mean 7°less lumbar lordosis) and more posterior pelvic tilt (mean 5°more sacral slope) in standing.…”
Section: Discussionsupporting
confidence: 81%
“…All patients were imaged by conventional radiography and by a slot scanning, x-ray system (EOS1; Biospace, Paris, France) [17,39,[41][42][43]70]. Implant orientations and contact patch to rim distance (CPR) [36] data were incorporated in each image.…”
Section: Standard Radiography and Eosmentioning
confidence: 99%
“…1), surgical positioning, and effects of ''edge loading'' [12,23,29,38,58,59,76]. Additionally, impingement, subluxation, and dislocation have always been unpredictable risk considerations [3,18,22,24,27,28,31,43,52,66,72,74,77,80]. Aggressive third-body abrasive wear can be one result of THA impingement [10,24,26,27,50].…”
Section: Introductionmentioning
confidence: 99%